The Consequences of State Intervention: Forced Relocations and Sámi Rights in Sweden, 1919–2012 - Patrik Lantto (Journal of Ethnology and Folkloristics)
From the late 19th century up until the post-war period, Swedish Sámi policy was dominated by an image of the Sámi as nomadic reindeer herders. As nomads, the Sámi connection to the land they used was generally considered weaker than that of the settled population, and forced relocations were part of the Sámi policy for several decades as a solution to international developments that affected reindeer husbandry. These relocations have had and still have an effect on reindeer husbandry in Sweden today. The article examines and analyses forced relocations of Sámi reindeer herders, and specifically the effects of these relocations on the situation in one Reindeer Herding District: Vapsten. Strong intra-Sámi conflicts in the district today have historical roots in the forced relocations to the area, and the article analyses these and the role of the state both in causing the conflicts as well as solving them.